(untitled) (Хабаршы. Психология және социология сериясы, 2015)
Creation of two integrating mechanisms: Customs Union and Com mon Free Market Zone favors forming fundamental conditions for accel erated transferring of three countries: Russia, Kazakhstan and Belarus to neoindustrial progress stage. The purpose of holding coordinated policy is to consistently advance to equal economic opportunities and mature competition with open customs borders and free capital flows. European Union has gone through a similar way during decades. Although having a higher economical development level that is similar customs, investment and tax policies. Our expert survey results make case history of reforms implemented under conditions of Cus toms Union. Expert survey showed that domestic entrepreneurs negatively reacted on challenges arisen in price formation related to joining Customs Union. To our view we have two major attitudes to the current situation. Particular paradox is that entrepreneurs understand that they are required to carry out radical reforms of economic structure to enable Kazakhstan to enter first fifty developed world countries. At the same time the current regu lated process of harmonization sometimes fails, there are no coordinated common economic and legal norms. If you take Customs Union as the first stage for integration in the form of creating common commodity market, then creation of Common Free Market Zone will landmark transition to form a production zone. All these express a new strategy of social and economi cal cooperation. This first of all regards to harmonization and unification of all norms and regulations, coordinated economical policy. At its basis there are objectively specified process of approximation, equalization and unifica tion of norms and rules of business activity in memberstates, ensuring free movement of goods, services and capital.